2012
DOI: 10.1063/1.4752729
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer enhancement with actuation of magnetic nanoparticles suspended in a base fluid

Abstract: Due to copyright restrictions, the access to the full text of this article is only available via subscription.In this study, we have experimentally demonstrated that heat transfer can be substantially increased by actuating magnetic nanoparticles inside a nanofluid. In order to materialize this, we have utilized a miniature heat transfer enhancement system based on the actuation of magnetic nanoparticles dispersed in a base fluid (water). This compact system consists of a pool filled with a nanofluid containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 35 publications
0
2
0
3
Order By: Relevance
“…Şekil 3 (a-b)'de manyetik kuvvetin olduğu ve olmadığı durumlardaki farklı konsantrasyonlardaki Fe3O4 nano-sıvısının ekserji yıkım oranları karşılaştırılmıştır. [24]. Nano-parçacık konsantrasyon etkisi çalışmaları daha çok havuz kaynama ya da akış kaynama şartlarında yapılmış olup tek-faz ısı transferi şartlarındaki etkisinden bahsedilmemiştir.…”
Section: Tek Fazlı Isı Transferi şArtlarındaki Ekserji Sonuçlarıunclassified
See 2 more Smart Citations
“…Şekil 3 (a-b)'de manyetik kuvvetin olduğu ve olmadığı durumlardaki farklı konsantrasyonlardaki Fe3O4 nano-sıvısının ekserji yıkım oranları karşılaştırılmıştır. [24]. Nano-parçacık konsantrasyon etkisi çalışmaları daha çok havuz kaynama ya da akış kaynama şartlarında yapılmış olup tek-faz ısı transferi şartlarındaki etkisinden bahsedilmemiştir.…”
Section: Tek Fazlı Isı Transferi şArtlarındaki Ekserji Sonuçlarıunclassified
“…Literatürde kümelenme ve çökelme sorunlarını aşmak için manyetik kuvvetle hareketlendirilen nano-sıvılar kullanılmıştır [20][21][22][23][24]. Şeşen vd.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Numerous studies have been carried out on passive and active heat transfer systems equipped with nanofluids to increase their efficiencies (Huminic et al, 2011;Morega et al, 2012;Rashidi et al, 2018bRashidi et al, , 2018aEl Bécaye Maïga et al, 2006). Because of the unique properties of nanofluid, they are being used in different applications such as fuel cells, engine cooling/vehicle thermal management, microelectronics and hybrid-powered engines (Sesen et al, 2012;Zakaria et al, 2015;Minkowycz et al, 2012). It has been found that the rheological behavior of nanofluids is very important in determining their suitability for convective heat transfer applications (Witharana et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ferrohydrodynamics, magnetorheology and magnetophoresis, which are relevant to a broad spectrum of applications. MMF can be useful for applications such as micromixing [3,4], actuation [5][6][7], magnetic separation [8,9], heat transfer enhancement [10,11], MEMS [12] and optofluidics [13]. MMF is also the guiding principle behind several biomedical applications involving nanocytometry-microcytometry [14,15], cell sorting [16,17], cell analysis [18,19], immobilization of enzymes [19,20], MRI [21] and magnetic fluid hyperthermia [22,23].…”
Section: Introductionmentioning
confidence: 99%